PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEKERJA CV. PUTRA JAYA DALAM PROYEK PENGGANTIAN SEGMENTAL PARTIAL GARIS MINYAK UTAMA - Saepudin, Asep; Gunawan, Ce (Universitas Putera Batam, 2024)
This study aims to determine the effect of leadership style and motivation on employee performance on Segmental Partial Replacement Main Oil Line Project. The sample in this study is the employees CV. Putra Jaya who are in the Segmental Partial Replacement Main Oil Line project. This research use quantitative method. Data collection techniques used were questionnaires. Data analysis techniques used in this study is multiple linear regression. Leadership Styke and Motivation simultaneously affect the performance of employees. Leadership style partially significant effect on employee performance, Motivation partially also have a significant effect on employee performance. Furthermore, the variable that has the most significant influence is the Leadership Style